IMPACT OF THE COVID-19 PANDEMIC ON URBAN DEVELOPMENT: A SYSTEMATIC REVIEW - Zhang, Jinyu; Mariney Mohd Yusoff; Tengku Adeline Adura Tengku Hamzah; Nisfariza Mohd Noor; Shi, Qinyu; Li, Xiaoya; Wang, Zhichao (Journal of Surveying, Construction and Property, 2025)
The COVID-19 pandemic gradually became prevalent globally in early 2020, affecting multiple aspects of lifestyle, transportation, and politics, and hitting the world economy hard. Due to the large population and economic activity densities, urbans are more vulnerable to more dangers. The influence of COVID-19 on urban areas is therefore widespread. The authors reviewed the literature after the first confirmed cases in Wuhan, China, to present a comprehensive evaluation of studies on the impact of the COVID-19 pandemic on urban development. The results show that studies on the impact of COVID-19 on cities are mainly related to five main topics, namely (1) environmental quality, (2) social impact, (3) economic impact, (4) urban residents, and (5) urban planning and management. While this shows the diversity of the research agenda, the first theme dominates, whereas the others remain relatively under-researched with little systematic research. This paper also has five more suggestions that can be used in planning and designing cities after COVID to help them grow in a way that is sustainable. Overall, the available research indicates that the COVID-19 crisis offers governments and planners a powerful chance to better respond to future emergencies and disasters and to promote sustainable and healthy urban development.